2011
DOI: 10.1111/j.1461-9563.2011.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Protected raspberry production alters aphid–plant interactions but not aphid population size

Abstract: 1 Aphid population dynamics in crops are often driven by interactions with their host plants, which can be extensively influenced by environmental change. Protective environments (i.e. plastic tunnels) are now frequently used for soft fruit production, which may affect the localized climate and alter such interactions. This two year study on red raspberry (Rubus idaeus) addressed how protected environments affected two aphid species; the large raspberry aphid Amphorophora idaei (LRA) and the small raspberry ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The aphid abundances were fairly typical for this aphid species (e.g. Johnson et al , ), although particularly low values might have resulted from slow aphid development, reduced fecundity or high mortality on some genotypes. A recent field study indicated a positive association between aphid abundance and leaf trichome density (Graham et al , ), which might be considered surprising; elevated leaf trichome density frequently has a negative effect on the abundance of aphids feeding on other crop species (Webster et al , ; Khan et al , ), although sap‐feeding herbivores can be unaffected by leaf physical traits (Carmona et al , ).…”
Section: Discussionmentioning
confidence: 86%
“…The aphid abundances were fairly typical for this aphid species (e.g. Johnson et al , ), although particularly low values might have resulted from slow aphid development, reduced fecundity or high mortality on some genotypes. A recent field study indicated a positive association between aphid abundance and leaf trichome density (Graham et al , ), which might be considered surprising; elevated leaf trichome density frequently has a negative effect on the abundance of aphids feeding on other crop species (Webster et al , ; Khan et al , ), although sap‐feeding herbivores can be unaffected by leaf physical traits (Carmona et al , ).…”
Section: Discussionmentioning
confidence: 86%
“…This is particularly true for crops grown under cover (e.g. glasshouse, polytunnel), which is an increasingly common practice for enhancing productivity (Wittwer & Castilla, ; Johnson et al ., , ), because natural enemies work more effectively in closed environments (McMenemy et al ., ). Even in noncovered agricultural crops, top‐down regulation of herbivore populations is both important and increasingly encouraged (Stiling & Cornelissen, ; Van Driesche, ).…”
Section: Discussionmentioning
confidence: 99%
“…Confining aphids on plants necessitated the use of potted plants in closed chambers, which might result in artificially high plant growth responses to CO 2 enrichment (Ainsworth et al ., ). Given, however, that >90% of raspberry production takes place in closed polytunnels that buffer environmental fluctuations (Johnson et al ., , ), this is perhaps a less relevant concern in this system because chambers have similar effects. Moreover, the use of large pots and potting media minimized restrictions to root growth and the potential for hypoxic conditions, as advocated by Passioura ().…”
Section: Discussionmentioning
confidence: 99%
“…This increase in resource demand has been linked to a compensatory increase in photosynthetic rate [28,29], which can alter the growth and physiology of the plant, potentially inducing an increase in the biomass of plants exposed to herbivory [30 -32]. Such increases in growth could redirect resources away from sink tissues [32] such as the stolons and into structural tissues such as stems, although this effect did not extend to a decline in tuber mass. Response of tuber mass to aphid feeding was detected only when clone identity and soil treatment were taken into account, but there was no discernible pattern to this variation and any explanation for these effects, for example, owing to clonal differences in feeding rate and manipulation of resource allocation, are speculative.…”
Section: Discussionmentioning
confidence: 99%